Exact solutions related to nonminimal gravitational coupling - de Sousa, C. M G [UNESP]; Mendonça da Silveira, F. E. [UNESP] (Elsevier, 1995)
We obtain exact analytic solutions for a typical autonomous dynamical system, related to the problem of a vector field nonminimally coupled to gravity. © 1995.